Spencer Bower - reliance-based estoppel : the law of reliance-based estoppel and related doctrines /: the law of reliance-based estoppel and related doctrines. (2017) - Feltham, Piers; Leech, Tom; Crampin, Peter; Winfield, Joshua
No abstract available